2015
DOI: 10.1093/jxb/erv481
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of abscisic acid signaling pathway facilitates aphid xylem absorption and osmoregulation under drought stress

Abstract: HighlightAphid fecundity is curtailed in drought-stressed plants primarily via reduced water status; however, activation of ABA signaling by drought cross-talks with SA and JA signaling to reduce induced plant resistance effects on aphid fecundity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 61 publications
4
70
0
Order By: Relevance
“…He et al [23] have shown that the activity of PAL (an enzyme involved in lignin synthesis) is induced in chrysanthemum by aphid feeding, which implies a contribution of lignin to aphid tolerance. Aphids need to access the phloem for nutrient and to the xylem to avoid an excessive build-up of osmotic pressure resulting from their consumption of sugar-rich phloem fluid [24]. Thus, the great lignification of the CmMYB19 over-expressors may make it more difficult for the aphid stylet to gain access, and thus could act as the brake on aphid multiplication observed in the CmMYB19 over-expressors.…”
Section: Discussionmentioning
confidence: 99%
“…He et al [23] have shown that the activity of PAL (an enzyme involved in lignin synthesis) is induced in chrysanthemum by aphid feeding, which implies a contribution of lignin to aphid tolerance. Aphids need to access the phloem for nutrient and to the xylem to avoid an excessive build-up of osmotic pressure resulting from their consumption of sugar-rich phloem fluid [24]. Thus, the great lignification of the CmMYB19 over-expressors may make it more difficult for the aphid stylet to gain access, and thus could act as the brake on aphid multiplication observed in the CmMYB19 over-expressors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ABA can suppress SA-dependent defenses (De Torres Zabala et al, 2009; Jiang et al, 2010; Cao et al, 2011). Concerning aphids, there are several reports that infestation induced ABA levels or ABA-regulated gene expression in Glycine max , M. truncatula , and A. thaliana (Studham and Macintosh, 2013; Guo et al, 2015; Sun et al, 2015; Hillwig et al, 2016). In contrast, another study showed that ABA levels in M. truncatula were not affected or even reduced by A. pisum feeding (Stewart et al, 2016) a pattern we also found in our study, where ABA levels in aphid-infested plants were generally lower or very similar than those in control plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, ABA could play other roles in plant-aphid interactions. For instance, ABA-driven stomatal closure could be advantageous for aphids under dry conditions since it maintains plant turgor and so facilitates aphid feeding (Guo et al, 2015). However, by causing reductions in photosynthetic activity, ABA-induced closure of stomata could decrease the carbohydrate supply available to aphids.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors inactivate plant PP2Cs, such as ABI1 and ABI2 , which are known to suppress ABA signalling (Ma et al 2009; Park et al 2009). Recently, it was shown that aphids feeding on A. thaliana and the legume Medicago truncatula increase ABA content in the plants (Guo et al 2016; Hillwig et al 2016). Furthermore, M. persicae aphid population development was negatively affected on ABA-deficient mutants compared to wild-type A. thaliana plants (Kerchev et al 2013; Hillwig et al 2016).…”
Section: Discussionmentioning
confidence: 99%